2019
DOI: 10.1111/jvs.12750
|View full text |Cite
|
Sign up to set email alerts
|

The combined effects of an extreme heatwave and wildfire on tallgrass prairie vegetation

Abstract: Questions: Climate extremes are predicted to become more common in many ecosystems. Climate extremes can promote and interact with disturbances, but the combined effects of climate extremes and disturbances have not been quantified in many ecosystems. In this study, we ask whether the dual impact of a climate extreme and concomitant disturbance (wildfire) has a greater affect than a climate extreme alone. Location: Tallgrass prairie in the Konza Prairie Biological Station, northeasternKansas, USA. Methods:We q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 74 publications
1
7
0
Order By: Relevance
“…In a frequently burned mesic C 4 ‐dominated grassland (tallgrass prairie in Kansas, USA), experimentally imposed extreme drought resulted in a loss of forbs with rapid recovery of aboveground net primary productivity (ANPP) postdrought because of increased abundance of grasses (Hoover et al ). However, in the same C 4 ‐dominated grassland, wildfire during a naturally occurring extreme drought increased forb abundance postdrought (Ratajczak et al ). Furthermore, Koerner and Collins () showed that shifts in grass and forb relative cover were minimal in both mesic grasslands in North America and South Africa under short‐term experimental drought across different fire regimes.…”
Section: Introductionmentioning
confidence: 99%
“…In a frequently burned mesic C 4 ‐dominated grassland (tallgrass prairie in Kansas, USA), experimentally imposed extreme drought resulted in a loss of forbs with rapid recovery of aboveground net primary productivity (ANPP) postdrought because of increased abundance of grasses (Hoover et al ). However, in the same C 4 ‐dominated grassland, wildfire during a naturally occurring extreme drought increased forb abundance postdrought (Ratajczak et al ). Furthermore, Koerner and Collins () showed that shifts in grass and forb relative cover were minimal in both mesic grasslands in North America and South Africa under short‐term experimental drought across different fire regimes.…”
Section: Introductionmentioning
confidence: 99%
“…Many grasslands experience a complex disturbance regime that includes grazing, fire and periodic drought (Collins et al, 1998;Smith et al, 2016;Ratajczak et al, 2019). This complex disturbance regime partly determines the persistence of soil seed banks (Fenner & Thompson, 2005), and grassland species exhibit a wide spectrum of seed longevity.…”
mentioning
confidence: 99%
“…It is important to note that currently available data do not allow us to track the potential for within functional group transitions, such as shifts from a native to invasive annual grass. In a local field‐based study, Ratajczak et al (2019) noted a shift in the dominance of grasses versus forbs following wildfire during drought, which we could not assess. Continued advancements in data products will allow us to better unravel these complexities.…”
Section: Discussionmentioning
confidence: 79%
“…A more nuanced assessment of the relationships between variability in drought, vegetation, and wildfire is needed in the Great Plains to fully gauge the outcomes of large wildfires. Numerous small‐scale studies have documented the complex interactions between drought, fire, and vegetation composition (e.g., Fuhlendorf & Smeins, 1997; Ratajczak et al, 2019; Taylor et al, 2012; Twidwell et al, 2016). Wildfire characteristics like intensity and size are strongly influenced by drought (Krueger et al, 2015; Twidwell et al, 2016); however, the impacts of drought on fire are spatially and temporally heterogeneous.…”
Section: Discussionmentioning
confidence: 99%